PENGARUH LABA AKUNTANSI, KOMPONEN ARUS KAS, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN KELOMPOK LQ45 ( Periode 2015-2017 ) - Ibram Akbar Bani Saleh, 13.05.52.0148; Wahyud, Djoko (Students' Journal of Accounting and Banking, 2018)
The research aims to analyze the influence of accounting profit, cash flow of operating activities, cash flow of investment activity, cash flows of lending activities and firm size toward stock prices on LQ 45 Companies Listed in Indonesia Stock Exchange Periode 20152017. The population in this research was all LQ 45 Companies that listed in Indonesia Stock Exchange Period 2015-2017. Selection of Sample used purposive sampling method. The Analysis used in this research aremultiple linear regression model. The result showed that the F-test statistic shows that, between accounting profit, cash flow of operating activities, cash flow of investment activity, cash flow of lending activity and firm size jointly influence toward stock price. And the results of the testing of hypothesespartial evaluation shows accounting profit, cash flow of operating activities, cash flow of lending activity and firm size that there is a positive significant toward stock prices. While for, cash flow of investment activity, there is a negative significant toward stock price. Keywords: stock prices, of accounting profit, cash flow of operating activities, cash flow of investment activity, cash flows of lending activities and firm size